2010
DOI: 10.1136/vr.c3523
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of ear cytology in dogs with otitis externa

Abstract: Eighty-three dogs with clinical signs of otitis externa and with ear cytology revealing microbial organisms were studied. Samples were collected from both ears of each dog by inserting two swabs successively into each ear canal, rotating each once through 360 degrees and then rolling it out in a line on to a glass slide. For each animal, four single parallel smears (SPS) were made on one slide, which was then appropriately labelled to identify the animal as well as the order of the samples. The slides, one rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 29 publications
2
14
0
3
Order By: Relevance
“…There are also investigations affirming that female dogs suffered more commonly from external otitis (Houdshell & Henssey, 1972;Carlotti, 1991). Hayes et al (1987) did not observe any substantial differences between the genders with respect to the occurrence of otitis externa similarly to other studies which did not confirm sex predilection (Nuttal, 1998;Huang & Huang, 1999;Lehner et al, 2010). To the best of our knowledge, no study has reported effects of sex hormones on the incidence of ear diseases.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…There are also investigations affirming that female dogs suffered more commonly from external otitis (Houdshell & Henssey, 1972;Carlotti, 1991). Hayes et al (1987) did not observe any substantial differences between the genders with respect to the occurrence of otitis externa similarly to other studies which did not confirm sex predilection (Nuttal, 1998;Huang & Huang, 1999;Lehner et al, 2010). To the best of our knowledge, no study has reported effects of sex hormones on the incidence of ear diseases.…”
Section: Discussionmentioning
confidence: 57%
“…The structure of the ears is essential for the occurrence, development and outcome of ear diseases in small animals, confirmed also by other studies (Sharma & Rhoades, 1975;August, 1988;Logas, 1994;Hayes et al, 1987;Lehner et al, 2010). The probable reason is the lack of proper ventilation in the ear canal due to its closure by the dropped pinna and the maintenance of higher level of humidity (Nardoni et al, 2008).…”
Section: Discussionmentioning
confidence: 74%
“…21 While there is some evidence to suggest that dogs with pendulous ears have a higher risk of otitis externa, compared with dogs with erect ears, it appears that specific breeds tend to have a higher predisposition than others regardless of ear conformation. 22,23 For example, 1 study found that otitis externa is more common in Cocker Spaniels, Poodles, and German Shepherd Dogs, 24 and another found a higher prevalence in Golden Retrievers and West Highland White Terriers. 23 None of these breeds traditionally have their ears cropped, and their natural ear position varies between hanging and erect.…”
Section: Ear Croppingmentioning
confidence: 99%
“…22,23 For example, 1 study found that otitis externa is more common in Cocker Spaniels, Poodles, and German Shepherd Dogs, 24 and another found a higher prevalence in Golden Retrievers and West Highland White Terriers. 23 None of these breeds traditionally have their ears cropped, and their natural ear position varies between hanging and erect. At least 1 textbook on veterinary surgery 25 no longer includes detailed information on ear cropping in dogs because of ethical concerns associated with the procedure, with the authors indicating their support for the AVMA position statement against this procedure.…”
Section: Ear Croppingmentioning
confidence: 99%
“…), budding yeast ( Malassezia, Candida spp. ), in conjunction with neutrophils and DNA strands are commonly identified on cytological examination of otic exudate collected from ears with otitis externa . A common collection technique used in veterinary practice is to insert a cotton‐tipped swab into the vertical portion of the external ear canal.…”
Section: Introductionmentioning
confidence: 99%